2021
DOI: 10.3390/jcm10194320
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Use of Cyanoacrylate-Lipiodol Mixture for Peripheral Embolization: Properties, Techniques, Pitfalls, and Applications

Abstract: Endovascular embolization agents are particles and fluids that can be released into the bloodstream through a catheter to mechanically and/or biologically occlude a target vessel, either temporarily or permanently. Vascular embolization agents are available as solids, liquids, and suspensions. Although liquid adhesives (glues) have been used as embolic agents for decades, experience with them for peripheral applications is generally limited. Cyanoacrylates are the main liquid adhesives used for endovascular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…In APF, where flow rate is high, lower cyanoacrylate/ Lipiodol ratio of 1:1 or 1:2 may be used to prevent nontarget distal penetration. [17] In cases of multiple small arterial feeders supplying the fistula not amenable for subselective catheterization, injection of collagen-thrombin mixture (D-Stat) can be used to occlude the portal venous outflow of the APF. [18] Teaching points…”
Section: Discussionmentioning
confidence: 99%
“…In APF, where flow rate is high, lower cyanoacrylate/ Lipiodol ratio of 1:1 or 1:2 may be used to prevent nontarget distal penetration. [17] In cases of multiple small arterial feeders supplying the fistula not amenable for subselective catheterization, injection of collagen-thrombin mixture (D-Stat) can be used to occlude the portal venous outflow of the APF. [18] Teaching points…”
Section: Discussionmentioning
confidence: 99%
“…However, vessel remodeling can take place, leading to glue migration in the blood vessels and recanalization. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Since less amount of cyanoacrylate is used, the risk of developing complications will also decrease. 7 CAC therapy has been associated with a phlebitis-like reaction, thought to be a type IV hypersensitivity reaction. Park et al reported on the features differentiating phlebitis-like abnormal reactions from classic phlebitis for patients after CAC therapy for incompetent saphenous veins, which defined the former as an unusual skin reaction over the treated area several days after CAC therapy.…”
Section: Discussionmentioning
confidence: 99%